1994
DOI: 10.1007/bf00221141
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the salt tolerance of Triticum turgidum L. by the Kna1 locus transferred from the Triticum aestivum L. chromosome 4D by homoeologous recombination

Abstract: Durum wheat, Triticum turgidum L. (2n= 4x=28, genome formula AABB) is inferior to bread wheat, T. aestivum L. (2n=6x=42, genome formula AABBDD), in the ability to exclude Na(+) under salt strees, in the ratio of the accumulated K(+) to Na(+) in the leaves under salt stress, and in tolerance of salt stress. Previous work showed that chromosome 4D has a major effect on Na(+) and K(+) accumulation in the leaves of bread wheat. The 4D chromosome was recombined with chromosome 4B in the genetic background of durum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
87
3

Year Published

1997
1997
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 151 publications
(96 citation statements)
references
References 12 publications
6
87
3
Order By: Relevance
“…3), experiments in soil in a flood bench (Gorham & Bridges, unpublished), and from the field data of Dvorak et al (1994), it is also apparent that the Knal gene is not the only factor controlling ion accumulation or yield under salinity. Indeed, the recombinant lines vary considerably in yield under non-saline conditions (Dvorak et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3), experiments in soil in a flood bench (Gorham & Bridges, unpublished), and from the field data of Dvorak et al (1994), it is also apparent that the Knal gene is not the only factor controlling ion accumulation or yield under salinity. Indeed, the recombinant lines vary considerably in yield under non-saline conditions (Dvorak et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…In general, recombinant lines which exhibited the enhanced K'^/Na'*^ trait were slightly more tolerant of salinity in the field than recombinants lacking the trait (Dvorak et al, 1994). There was however, considerable variation between individual lines, w^hich is understandable considering that they originated from a hybrid involving into very different genetic backgrounds.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…/Na ? ratio has been repeatedly referred as an important indicator for plant salt tolerance (Gorham et al 1991;Gaxiola et al 1992;Dvorak et al 1994;Maathuis and Amtmann 1999;Cuin et al 2003;Colmer et al 2006); however, less direct experimental evidence can be found to support it due to no proper measuring protocol. The major hurdle is the lack of appropriate and convenient techniques to enable such compartmentation analysis for differentiating K ?…”
Section: Oxidative Stress Induced By Salt Stressmentioning
confidence: 99%
“…For example, durum wheat has a much higher level of salt uptake and much lower level of salt tolerance compared with bread wheat. Durum lacks the Na + exclusion trait (Dvorak et al 1994;Munns et al 2000a), which accounts for the better performance of bread wheat than durum wheat on salinesodic soils (Dang et al 2004c;Rathjen et al 1999), whereas barley can tolerate high Na + levels compared with both bread and durum wheat (Dang et al 2004c;Munns et al 2000b). Subsoil constraints restrict rooting depth, preventing water uptake by plants.…”
Section: Plant Adaptationmentioning
confidence: 99%